Human Rights and Assisted Reproductive Technologies (ART): A Contractarian Approach - de Araujo, Marcelo (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
What are human rights? Do they exist? I propose to answer these questions by advancing a contractarian account of human rights. I focus on the human right to found a family and have children. I also show how the contractarian approach to human rights can explain the current relevance of reproductive rights in the human rights discourse, and how the emergence of ART (Assisted Reproductive Technologies) has contributed to this shift. The contractarian account of human rights asks, firstly, the following question: which basic needs and desires can be ascribed to any human being regardless of gender, nationality, sexual orientation, age, ethnicity etc.? Having an interest, for instance, in preserving one’s own bodily integrity, freedom, and private property qualifies as a basic human need or basic desire. But a basic human need or desire does not constitute in itself a human right. Secondly, the contractarian account of human rights asks, then, which basic human needs or basic desires individuals and states representatives would consider so important that they would agree to create institutional frameworks, both at the domestic and international level, in such a way as to enable individuals to pursue the fulfilment of their basic needs or desires without state interference. Human rights exist and can only be claimed in the context of these normative frameworks.